Os papéis das instituições participativas na estruturação das políticas públicas no Brasil - Almeida, Carla; Martelli, Carla Giani [UNESP]; Coelho, Rony (Universidade de Brasília. Instituto de Ciência Política, 2021)
Based on an approach that emphasizes the mutual constitution between political-relational and technical-administrative capacities, this article explores the roles of Participatory Institutions (PIs) in the policy construction and change in Brazil. Based on six policy areas, we propose the following typology of roles to understand variation in the effect of PI on policy institutionalization: reform, foundation or episodic/contingent roles. We argue that the combined action of three factors - pre-existing technical and administrative capacities, political opportunities and of the characteristics of policy communities - helps to understand the variation.

A partir de uma abordagem que enfatiza a mútua constituição entre capacidades político-relacionais e técnico-administrativas, o objetivo deste artigo é qualificar o papel que as Instituições Participativas (IPs) assumiram na estruturação e na trajetória das políticas públicas no Brasil. Com base em seis áreas de políticas, sugerimos a seguinte tipologia para compreender a variação que as IPs tiveram na institucionalização das políticas: papel reformador, fundante ou episódico/contingencial. Argumentamos que a ação combinada de três fatores - capacidades técnico-administrativas pré-existentes, oportunidades políticas e dinamismo e configuração das comunidades de políticas - ajuda a compreender a variação.
The roles of participatory institutions in structuring public policies in Brazil
Keywords: Participatory institutions; Public policies; Institutionalization; State capacities; Instituições participativas; Políticas públicas; Institucionalização; Capacidades estatais